(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the importance and pedagogical problems of an individual approach in the process of intellectual development of future primary school teachers. Effective methods of intellectual development of students, pedagogical problems, innovative technologies and methodological solutions are considered. It is emphasized that an individual approach serves to increase the creative and cognitive potential of future teachers, as well as to improve the quality of the pedagogical process.